Public Service Accountability At The Regional Drinking Water Company (PDAM) Of Sidoarjo Regency In Providing Clean Water - Dimas Pebrianto; Ika Devy pramudiana; Nihayatus Sholichah (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the accountability of public services at the Sidoarjo Regency Water Company (PDAM) in providing clean water to the community. The research focuses on service transparency, responses to public complaints, accountability in services, as well as challenges and efforts to improve accountability in public services. This study applies a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation with informants consisting of PDAM employees and community members who use clean water services. Data analysis using the Miles and Huberman interactive model consists of data reduction, data presentation, and conclusion drawing. The research findings indicate that public service accountability at the Sidoarjo Regency PDAM has been carried out through the provision of service information, public complaint channels, and responses to customer complaints. Transparency in services is implemented through direct and digital media, while service responsiveness is realized through the handling of public complaints by service units and technical officers in the field. However, service implementation still faces challenges such as limited human resources, the condition of the aging water distribution network infrastructure, and the unoptimized access to digital services for the community. This study recommends improving infrastructure quality, strengthening digital technology-based service systems, and enhancing human resource capabilities to support more transparent, responsive, and accountable public services.